Extending a Geographic Lens Towards Climate Justice, Part 1: Climate Change Characterization and Impacts. Issue 3 (15th March 2013) - Burnham, Morey; Radel, Claudia; Ma, Zhao; Laudati, Ann
Abstract There has been a recent increase of interest within the academic literature on the justice issues posed by climate change and the human responses to its present and forecasted effects. This literature is partially shaped by debates from environmental justice scholarship, but also has roots in various subfields of geography. In two parts (here and in a subsequent article), we review and synthesize the recent literature by asking what climate justice concerns have been identified within three related realms: (i) the characterization of climate change itself and the assignment of responsibility for that change; (ii) the differential or uneven impacts of climate change; and (iii) the actions taken to address the problems associated with climate change, including mitigation and adaptation. Here, in Part 1, we provide a basic outline of justice concepts; we address the characterization of climate change and the associated discursive framings; and we discuss the uneven impacts of climate change with a focus on the conceptualization of vulnerability. We suggest that the field of geography has much to offer to the debate on climate justice because of its unique understandings of the human‐environment relationship based on a longstanding engagement with the spatiality and scale of environmental change, the corresponding human impacts, and the conceptual inseparability of nature and society. We identify, across Part 1 and Part 2, the need for a more comprehensive theory of justice to inform climate justice considerations – one that pays more attention to linked procedural, recognition, and scalar concerns.